(untitled) (Journal for Studies in Humanities and Social Sciences, 2019)
This article reports on the initial planning stages of a Namibian German dictionary project, i.e. a dictionary that would primarily provide semantic information in Standard German about Namibian German lexical items. The concept of Namibian German is explained, and existing dictionaries of Namibian German are briefly surveyed. The theoretical framework is that of a new lexicographic theory, i.e. the theory of lexicographical communication. Within this framework, a new classification of three types of dictionary purposes is introduced, i.e. macro-contextual purposes, meso-contextual purposes and micro-contextual purposes. The focus then shifts to the development of a basic micro-structure for the dictionary, which refers to a set of lexicographic messages encoded in lexicographic utterances that would be included in a dictionary article in order to answer specific potential target user questions. Pertinent elements of the theory of lexicographical communication are worked out to develop a basic microstructure for the equivalent relation of full equivalence. This demonstrates that the theory can be applied generatively, i.e. to develop a dictionary model starting from a set of empirically identified user questions relating to a particular user situation. In the process, a formal link between user questions, consultation objectives, lexicographic messages and lexicographic utterances is established. This is followed by an overview of how a basic microstructure could be amplified to ensure successful lexicographical communication.